2015
DOI: 10.1186/s13071-015-0759-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and protozoal agents of canine vector-borne diseases in the blood of domestic and stray dogs from southern Portugal

Abstract: BackgroundThe so-called canine vector-borne diseases (CVBD) are caused by a wide range of pathogens transmitted by arthropods. In addition to their veterinary importance, many of these canine vector-borne pathogens can also affect the human population due to their zoonotic potential, a situation that requires a One Health approach. As the prevalence of vector-borne pathogens in cats from southern Portugal has been recently evaluated, the aim of the present study was to assess if the same agents were present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 53 publications
5
31
3
1
Order By: Relevance
“…In Brazil, previous studies have shown that the prevalence of CVBDs in dogs in urban areas has varied from absence to 91.2% (Lasta et al, 2013;Spolidorio et al, 2013;Vieira et al, 2013b). Although the neighborhood dogs of the present study had comparatively lower CVBD prevalence (Vieira et al, 2013b;Azzag et al, 2015), the wide differences in CVBD prevalence may be explained by the populations studied, lifestyles, environmental occurrence of vectors and diseases, diagnostic tests used and vector competence of ticks from the Rhipicephalus sanguineus group (Balakrishnan et al, 2014;Maia et al, 2015;Moraes-Filho et al, 2015). As observed here, infection by CVBDs may occur in the absence of clinical signs (Joppert et al, 2001;Maggi et al, 2014;Azzag et al, 2015) or hematological changes (Novacco et al, 2010;Balakrishnan et al, 2014;Moraes-Filho et al, 2015).…”
Section: Introductioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In Brazil, previous studies have shown that the prevalence of CVBDs in dogs in urban areas has varied from absence to 91.2% (Lasta et al, 2013;Spolidorio et al, 2013;Vieira et al, 2013b). Although the neighborhood dogs of the present study had comparatively lower CVBD prevalence (Vieira et al, 2013b;Azzag et al, 2015), the wide differences in CVBD prevalence may be explained by the populations studied, lifestyles, environmental occurrence of vectors and diseases, diagnostic tests used and vector competence of ticks from the Rhipicephalus sanguineus group (Balakrishnan et al, 2014;Maia et al, 2015;Moraes-Filho et al, 2015). As observed here, infection by CVBDs may occur in the absence of clinical signs (Joppert et al, 2001;Maggi et al, 2014;Azzag et al, 2015) or hematological changes (Novacco et al, 2010;Balakrishnan et al, 2014;Moraes-Filho et al, 2015).…”
Section: Introductioncontrasting
confidence: 49%
“…A previous study on owned dogs did not show any significant associations between hemoplasma infection and anemia, ectoparasite infestation, gender and clinical status (Tennant et al, 2011), thus corroborating the findings from the neighborhood dogs of the present study. Although neighborhood dogs with outdoor lives in urban areas may be at higher risk of exposure to tickborne pathogens (Cardoso et al, 2012;Vieira et al, 2013b;Maia et al, 2015), only 1/7 (14.3%) of the dogs infected by M. haemocanis and 1/9 (11.1%) by 'Ca. M. haematoparvum' were infested by ticks.…”
Section: Introductionmentioning
confidence: 99%
“…El-Dakhly et al (2013) detected the parasite in 45 (23.56%) naturally infected dogs from Japanese islands and peninsulas by Giemsa-stained blood smears and 81 (41.33%) by Polymerase Chain Reaction (PCR), suggesting molecular techniques as a more sensitive diagnostic method than blood smear. On other hand, Maia et al (2015) detected low occurrence (31/101, 3.07%) of H. canis infection in dogs from Portugal by PCR, as well as Aktas et al (2015) in Turkey (3/285, 1%). In Israel, observed a low range of infected monocytes and neutrophils (0.45-3.78%), however, 50% of all monocytes were coinfected with E. canis morulae.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever available, data on sex, breed, coat length, coat colour, age, use of insecticides and presence of clinical signs compatible with leishmaniosis (namely muscular atrophy, cutaneous lesions, epistaxis, lameness, lymphadenomegaly, onychogryphosis, ocular lesions, pale mucous membranes or weight loss; [20]) were recorded for each dog. Blood and serum samples were obtained from previous epidemiological studies regarding exposure to L. infantum or Toscana and sand fly fever Sicilian viruses [21][22][23][24].…”
Section: Animalsmentioning
confidence: 99%
“…Four discs of filter paper (4 mm in diameter each) were incubated with lysis buffer (150 μl) and 1.5 μl of proteinase K (20 mg/ml). Further DNA extraction followed the kit manufacturer's instructions [24]. The saline samples containing eluted conjunctival cells were centrifuged at 3824×g for 10 min, and the pellets resuspended in 90 µl lysis buffer containing 10 µl of 2 mg/ml proteinase K. After 2 h incubation at 56 °C, the samples were incubated for 10 min at 95 °C and then centrifuged at 17,949×g for 10 min.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%